Indications for Thrombolytic Therapy in Acute Pulmonary Embolism - Dieck, John A. (1989)
Pulmonary thromboembolism is commonly misdiagnosed and is associated with significant morbidity and mortality both in the early and late stages. A major cause of late morbidity is chronic pulmonary hypertension. Although the incidence of chronic thromboembolic pulmonary hypertension is unknown, there is anatomic and physiologic evidence that it is responsible for a significant degree of the late morbidity and mortality following acute pulmonary embolism. In the absence of underlying cardiopulmonary disease, pulmonary artery pressure is a useful indicator of the severity of acute pulmonary embolism and of the patient's prognosis. Thrombolytic agents accelerate the lysis of the thromboemboli, offer an excellent alternative to emergency embolectomy, and are likely to decrease the incidence of chronic pulmonary hypertension. All currently available agents have been shown to be effective and have similar bleeding-complication profiles. In this review, we discuss the natural history and pathophysiology of pulmonary thromboembolic disease, as well as applications of thrombolytic therapy in the treatment of acute pulmonary embolism. (Texas Heart Institute Journal 1989;16:19-26)